ANALISIS FAKTOR YANG MEMPENGARUHI PERILAKU PEMILIH DALAM PEMILIHAN WALIKOTA TAHUN 2015 DI KOTA SOLOK PROVINSI SUMATERA BARAT - Liza Mayolla; Sri Erlinda; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research to have as background that any have a number of communities were apathetic to the election of the mayor and campaign to further high light the image of the candidates then talked about their performances and programs of pair candidate. They are constructive the image more, by doing activity that unusual carried out before they running as mayor. So, there are still many people who don’t knowing about their work programs. The formulation of this research is “What Are the Factors Influence the Behavior of Voters towards Mayoral Election In 2015 At Solok, West Sumatera”. The objective of this research is to know the factors of the voters’ behavior towards mayor election in 2015 at Solok, West Sumatera. Based on the result of this research, it show that factors that influence the behavior of voters towards mayoral election in 2015 at Solok, West Sumatera is vision, Mission, Religion of Muslim, intellectual ability, good attitude and the behavior, breakthrough that ever done, charismatic cases of legal that befall, their background life , their promises during they did campaign, their experienced about political, their job background, their popularity, background of their political parties, their age, their property assets, banners, how their parties do work to persuade the communities, their nota bane, and their male gender.Keyword: Analysis, Behavior of Voters